Potential Nephrotoxicity of Lisinopril and Valsartan on Patients with Congestive Heart Failure - Sarini Pani; Melisa I. Barliana; Eli Halimah; Venice Chaeriadi; Mally G. Sholih (Universitas Padjadjaran, 2017)
Lisinopril (angiotensin converting enzyme inhibitor) and valsartan (angiotensin II receptor blocker) are the first-line treatment for patients with congestive heart failure (CHF). These two drugs potentially cause side effects on renal functions. However, limited information was available regarding the comparison of potential nephrotoxicity of these drugs in Indonesian CHF patients. This research was aimed to compare the potential nephrotoxicity between lisinopril and valsartan in outpatients with CHF at a hospital in Palu, Indonesia. This was an observational study conducted during April-May 2015. Potential nephrotoxicity were assessed by measuring serum creatinin (SCr) and blood urea nitrogen (BUN). Data were obtained from Cardiology Unit from a hospital in Palu, Indonesia. Statistical analysis was conducted using T-test and Mann-Whitney test. The increasing trend of SCr and BUN were observed in lisinopril-treated patients with the mean of increase were 21% and 59%, respectively. Relatively higher increase was observed in valsartan treatment group with 47% and 51% in SCr and BUN, respectively. The analysis showed that there were significant differences in SCr level between lisinopril and valsartan groups (p=0.001), but the opposite results observed in BUN parameter (p=0.697). Therefore, valsartan was potentially more nephrotoxic than lisinopril based on the increase of SCr parameter. Thus, lisinopril is recommended for CHF patients who are particularly at high risks of having renal impairment. Keywords: lisinopril, valsartan, nephrotoxicity, congestive heart failure